Kompetensi PPL Mahasiswa Prodi Pendidikan Matematika Umrah Ditinjau dari Perspektif Guru Pamong - Rezky Ramadhona; Mirta Fera (Universitas Suryakancana, 2020)
The purpose of this study is to determine the basic competencies students have as prospective teachers at PPL at school. This type of research is a quantitative descriptive study. The data collection technique is using a perspective teacher questionnaire with data collection instruments is a questionnaire sheet. The results of this study indicate that student competencies at PPL are in the category of competencies. The achievement level of student pedagogy competence is 82.74% with the competent category, personality competence is 87.00% with the competent category, social competence is 85.23% with the competent category and Professional competence is 81.76% with the competent category.Keywords: Student Competencies at PPL, Perspective, Tutor Teacher